2019
DOI: 10.1002/anie.201814016
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Friedel–Crafts Alkylation Using a Promiscuous Biosynthetic Enzyme

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 34 publications
(17 reference statements)
2
73
0
2
Order By: Relevance
“…We set out to investigate whether BrtB, the only enzyme in the brt gene cluster with no ascribed function, could be responsible for ester formation. Following the protocol reported by Schultz et al 15 , we expressed and purified a Strep-Tag©-recombinant version of BrtB (NStrep-BrtB) in Escherichia coli BL21 DE3 Rosetta cells and tested its ability to convert 1 and 2 into 3 in vitro. We found that adding NStrep-BrtB to a reaction mixture composed of 1, 2 and Ca 2+ and Mg 2+ -containing buffer 12,15 was necessary and sufficient to generate diester 3 as well as monoester(s) 6a and/or 6b (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We set out to investigate whether BrtB, the only enzyme in the brt gene cluster with no ascribed function, could be responsible for ester formation. Following the protocol reported by Schultz et al 15 , we expressed and purified a Strep-Tag©-recombinant version of BrtB (NStrep-BrtB) in Escherichia coli BL21 DE3 Rosetta cells and tested its ability to convert 1 and 2 into 3 in vitro. We found that adding NStrep-BrtB to a reaction mixture composed of 1, 2 and Ca 2+ and Mg 2+ -containing buffer 12,15 was necessary and sufficient to generate diester 3 as well as monoester(s) 6a and/or 6b (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the role played by the brt-encoded CylK homolog (BrtB) has remained unclear. The reasons for this are twofold: first, the action of a CylK homolog is not necessary to explain the biosynthesis of currently known bartolosides 13,14 ; second, CylK requires a free C-2 resorcinol as a nucleophile 12,15 , a position that is unavailable (it is alkylated) in the bartolosides. Here, we show that BrtB is an O-alkylating enzyme that catalyzes the esterification of free (non-activated) fatty acids with the chlorinated positions found in the bartolosides, generating a diversity of fatty acid-bartoloside esters (Fig.…”
mentioning
confidence: 99%
“…Enzymes are potent biocatalysts that are able to carry out numerous chemical transformations with remarkable chemo‐, regio‐ and stereo‐selectivity . The intrinsic sustainability of enzymatic processes along with the use of green reaction conditions such as absence of potentially toxic solvents, and activation with non‐conventional sources of energy has expanded the use of biocatalysis in both chemical industries and in academic institutions, focusing in drug discovery and in the synthesis of molecules with relevant biological activity .…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes are potent biocatalysts that are able to carry out numerous chemical transformations with remarkable chemo-, regio-and stereo-selectivity. [1][2][3][4][5] The intrinsic sustainability of enzymatic processes along with the use of green reaction conditions such as absence of potentially toxic solvents, and activation with non-conventional sources of energy has expanded the use of biocatalysis in both chemical industries and in academic institutions, focusing in drug discovery and in the synthesis of molecules with relevant biological activity. [6][7][8] Recent developments in protein engineering and enzyme directed evolution, [9,10] together with the availability of efficient methods for the production of recombinant molecules, have led to rapidly expanding new fields in biocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Friedel-Crafts alkylation has been an important method for preparing substituted aromatics from the past to the present days [1][2][3]. Among these classical, but practical alkylation reactions, the homogeneous benzylation of aromatic hydrocarbons by benzyl alcohol (BzOH) or benzyl chloride (BzCl) is one of the significant reaction processes for the preparation of diphenylmethane (DPM) and its substituted derivatives (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%